Crafting Career-Ready Curriculum Vitae: A Genre-Based Instruction for Culinary Students - Julian Adhitama (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
One of the requirements for vocational students' job readiness is the ability to create a curriculum vitae in English, primarily to fulfill the overseas job market. Therefore, this study explores further how to implement genre-based instruction in teaching CV writing to help understand and identify barriers that may occur in the teaching process, especially in culinary competency vocational high schools. This research used a qualitative case study approach. The research was conducted in a private vocational school in Bandung, Indonesia. Data collection techniques used included the observation of culinary competence in class XII, the interview of an English teacher, and field notes during the observation conducted by the researcher. The results showed that the implementation of genre-based instruction in one rotation for each step of the Building Knowledge of the Field (BKoF), Modeling of the Text (MoT), Joint Construction of the Text (JCoT), and Independent Construction of the Text (ICoT) genres was not enough for students to apply what they had learned. This is because it was the first time the students were exposed to genre-based learning. Although they paid more attention in class, the students lacked the knowledge and confidence to write their CVs in English. This study recommends that future researchers provide more rotation and implement the suggestions from this study when implementing genre-based learning.